PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH DAN LAIN-LAIN PENDAPATAN ASLI DAERAH YANG SAH TERHADAP BELANJA DAERAH DI KABUPATEN DAN KOTA PROVINSI JAMBI - ABDUL WAHAB; Tona Aurora L; Susfayetti (Magister Ilmu Akuntansi Universitas Jambi, 2016)
The purpose of this study was to test empirically the effect that there is a Local Taxes , Levies, and Other Revenue Expenditure Against The Legitimate Government Jambi partially and simultaneously Naturalness based research site, the type of study used survey research is a type of research. Survey methods used to find the effect of a particular treatment, the research methods used in this survey research approach is quantitative research methods. Quantitative research is in process the data using descriptive and inferential statistical methods. Descriptive statistics were used to analyze statistical data in ways that describe or depict the data that has been collected as is without intending to generally accepted conclusions or generalizations. The research hypothesis tested using Ordinary Least Squere method (OLS). With this analysis of the influence of independent variables on the dependent variable under study can be known. Regression equation models were used to test the hypothesis Local Taxes, Levies, and Other Revenue Authorised affect Expenditure in Jambi Province. Research results is that the partial: Local Taxes significant negative effect on local shopping districts / cities in Jambi Province during the period 2003 to 2012. 1.1 Thus the hypothesis which states that significantly influence the Local Tax Expenditures in the District and the City of Jambi province can not be accepted or rejected. Retribution significant negative effect on local shopping districts / cities in Jambi Province during the period 2003 to 2012. Thus the hypothesis which states that 1.2 Retribution significant effect on regional expenditure in the District and the City of Jambi province can not be accepted or rejected. Revenue (PAD) Other legitimate significant positive effect on local shopping districts/cities in Jambi Province during the period 2003 to 2012. 1.3 Thus the hypothesis which states that significantly influence the Local Tax Expenditures in the District and the City of Jambi Province acceptable. In Simultaneous, Local Taxes, Levies, and Other Local Revenue Authorised Expenditure positive impact on the county and city of Jambi. Local Taxes Levies , and Other Revenue Expenditure Against significant effect in the District and the City of Jambi Province.